The m-n distribution - A new closed-form physical channel fading model and performance of M-ary modulations - Yilmaz, Ferkan; Kucur, Oğuz (My University, 2009)
In this work, a new closed form physical channel fading model, which we term m-n distribution, is introduced. The m-n distribution includes many distributions known in literature as special cases such as Rayleigh, Weibull, Nakagami-m, Generalized Gamma distributions, etc and their reciprocal distributions. Its statistical properties such as Laplace, Mellin moment generating functions and fractional moments are obtained. In addition, symbol error rate performance of M-ary modulations is derived and the results are given for binary differential phase shift keying. © 2010 Elsevier B.V., All rights reserved.
2009 European Wireless Conference, EW 2009 -- Aalborg -- 79361
Keywords: Closed form; Differential phase-shift keying; Fractional moments; Generalized gamma distribution; M-ary modulation; Moment generating function; Nakagami-m; Physical channels; Rayleigh; Statistical properties; Symbol error rates; Weibull; Function evaluation; Phase shift keying; Weibull distribution